'She's sort of breathing': What linguistic factors determine call-taker recognition of agonal breathing in emergency calls for cardiac arrest?. (January 2018) - Riou, Marine; Ball, Stephen; Williams, Teresa A.; Whiteside, Austin; Cameron, Peter; Fatovich, Daniel M.; Perkins, Gavin D.; Smith, Karen; Bray, Janet; Inoue, Madoka; O'Halloran, Kay L.; Bailey, Paul; et al.
Abstract: Background: In emergency ambulance calls, agonal breathing remains a barrier to the recognition of out-of-hospital cardiac arrest (OHCA), initiation of cardiopulmonary resuscitation, and rapid dispatch. We aimed to explore whether the language used by callers to describe breathing had an impact on call-taker recognition of agonal breathing and hence cardiac arrest. Methods: We analysed 176 calls of paramedic-confirmed OHCA, stratified by recognition of OHCA (89 cases recognised, 87 cases not recognised). We investigated the linguistic features of callers' response to the question " is s/he breathing? " and examined the impact on subsequent coding by call-takers. Results: Among all cases (recognised and non-recognised), 64% (113/176) of callers said that the patients were breathing ( yes -answers). We identified two categories of yes -answers: 56% (63/113) were plain answers, confirming that the patient was breathing (" he ' s breathing "); and 44% (50/113) were qualified answers, containing additional information (" yes but gasping "). Qualified yes -answers were suggestive of agonal breathing. Yet these answers were often not pursued and most (32/50) of these calls were not recognised as OHCA at dispatch. Conclusion: There is potential for improved recognition of agonal breathing if call-takers are trained to be alert to any qualification following a confirmation that the patient is breathing.